Bismuth bronze composite wire material for arc cladding of sliding bearing as well as preparation process and application of bismuth bronze composite wire material
Through the continuous composite process of bismuth bronze composite wire and liquid phase channel with two-layer structure, the problems of brittle fracture and low arc cladding efficiency in bismuth bronze wire molding are solved, and high-strength bonding and low-defect arc melting are achieved The coating improves the application performance of bismuth bronze composite silk material.
Patent Information
- Application Number
- CN202411585442.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Bismuth bronze wire is prone to brittle fracture during the molding process, which makes it difficult to process. The existing arc cladding technology has problems of efficiency and pore defects.
Bismuth bronze composite wire material with a two-layer structure, the inner core is a high melting point tin bronze, and the outer layer is a low melting point tin bismuth binary alloy. It is prepared through a continuous composite process of liquid phase channel, using local supercooling and laser-arc Directional energy deposition technology forms a liquid phase channel, controlling the wire diameter and composition of the composite welding wire.
Improve the processing plasticity of bismuth bronze composite wire, reduce the risk of brittle fracture, significantly improve the edge wetting and pore defects of the arc cladding layer, enhance the bonding between tin bismuth alloy and tin bronze, and improve the composite welding wire strength and application value.
Smart Images

Figure CN119260239A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a bismuth-bronze composite wire material for arc cladding of sliding bearings and a preparation process and application thereof, belonging to the technical field of alloy materials. Background Art
[0002] Since copper and bismuth are not miscible, the softer bismuth is distributed on the copper matrix and has a self-lubricating effect. Therefore, as a bearing alloy material, it has a low friction coefficient, excellent wear resistance, and good application prospects. At present, the main research and development directions of bismuth bronze materials are bismuth bronze powder and bismuth bronze wire. Among them, when using bismuth bronze powder for laser cladding, the disadvantage is that due to the high reflectivity of copper-based materials to laser and the influence of powder utilization rate, laser cladding of copper-based materials still has obvious efficiency and pore defects. Arc cladding has better thermal efficiency and more advantages for the cladding processing of copper-based materials. However, there is a technical bottleneck in the research and development of bismuth bronze wire required for arc cladding: the bismuth in bismuth bronze exists in the form of a single phase, which is often enriched at the grain boundary of the copper phase, resulting in a decrease in the strength of the bismuth bronze material and a decrease in processing plasticity. Therefore, brittle fracture is very likely to occur during the wire forming process, and wire processing is extremely difficult. Summary of the invention
[0003] In view of the problem that brittle fracture is very likely to occur during the molding process of bismuth bronze wire in the prior art, the purpose of the present invention is to provide a preparation process of bismuth bronze composite wire for arc cladding of sliding bearings, and to separate copper and bismuth in the wire structure through the improvement of composition and process to prepare a composite welding wire. Specifically, the wire cross section is divided into two layers according to the melting point, the inner core is a high melting point, high strength tin bronze, and the outer layer is a low melting point, low strength tin-bismuth binary alloy; and the low melting point outer layer material is composited on the inner core tin bronze by a liquid phase channel continuous composite process.
[0004] At the same time, the present invention provides a bismuth bronze composite wire material for arc cladding of sliding bearings.
[0005] At the same time, the present invention provides an application of a bismuth bronze composite wire for arc cladding of a sliding bearing in a bearing alloy.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0007] A bismuth bronze composite wire for arc cladding of sliding bearings, the bismuth bronze composite wire comprising a two-layer structure, measured by weight percentage,
[0008] The inner core structure is tin bronze, with Sn content of 4.36%-7.24% and the balance being Cu;
[0009] The outer layer structure is a tin-bismuth binary alloy layer, wherein the Sn content is 30%-70%wt, and the Bi content is 30%-70%wt.
[0010] A preparation process of a bismuth bronze composite wire for arc cladding of sliding bearings comprises the following steps:
[0011] S1, pass the tin bronze wire through the tin bath;
[0012] S2, start the local cooling device to perform a local supercooling process;
[0013] S3, injecting tin-bismuth alloy liquid into the tin bath;
[0014] S4, after the tin-bismuth alloy liquid around the tin-bronze welding wire solidifies to form a solid-phase tin-bismuth alloy zone, the laser-arc directional energy deposition device is turned on, and a liquid phase channel centered on the tin-bronze welding wire is formed in the solidified tin-bismuth alloy through the laser-arc composite directional energy deposition process, and the tin-bronze welding wire begins to move from top to bottom at a speed of 5mm / s-15mm / s; the size of the bottom hole of the liquid phase channel is controlled by adjusting the laser energy to control the wire diameter of the bismuth-bronze composite welding wire; the tungsten needle electrode is a moving electrode that performs a circular motion around the tin-bronze welding wire, the tungsten needle electrode is 6-8mm away from the tin-bronze welding wire, and the rotation speed is 40-80r / min;
[0015] S5, drawing the bismuth-bronze composite welding wire to a diameter of 0.8-1.6 mm through a drawing process to obtain a bismuth-bronze composite wire for arc cladding of sliding bearings.
[0016] Preferably, the temperature of the local supercooling process is 40-45°C.
[0017] Preferably, the diameter of the tin bronze welding wire is 2-4 mm.
[0018] Preferably, the Sn content in the tin-bismuth alloy liquid is 30%-70%wt, the Bi content is 30%-70%wt, and the depth of the tin-bismuth alloy liquid in the tin bath is 5mm-10mm.
[0019] Preferably, the laser power of the laser-arc composite directional energy deposition process is 300W-600W, the arc current is 60A-70A, the voltage is 11V-12V, and the directional direction is that the arc acts fixedly toward the solid phase tin-bismuth alloy area, and the laser acts fixedly toward the bottom hole direction.
[0020] An arc cladding process for bismuth bronze composite wire for arc cladding of sliding bearings, with a current of 90A, a voltage of 12V, a swing frequency of 0.6Hz, a swing width of 25mm, and a speed of 6cm / min.
[0021] The arc cladding layer obtained by the arc cladding process of the present invention has the following components by weight percentage: Bi: 2.17-5.66%, Sn: 6.43-11.76%, and the balance is Cu.
[0022] Preferably, the arc cladding layer obtained by the arc cladding process of the present invention further comprises one or more of Cr, Zr, Ti and P, and the total content of one or more of Cr, Zr, Ti and P is 0.05-0.08% by weight.
[0023] The invention discloses an application of a bismuth bronze composite wire for arc cladding of sliding bearings in bearing alloys.
[0024] Preferably, constant temperature circulating cooling water at 40-45° C. is introduced into the cooling device.
[0025] Preferably, the tin-bronze welding wire is 2-4 mm, the thickness of the tin-bismuth alloy layer after compounding is 0.04-0.08 mm, and the thickness of the tin-bismuth alloy is 0.015-0.03 mm when drawn to 0.8-1.6 mm.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. Currently, there is no mature technology for the preparation of bismuth bronze welding wire. Similar to this technical solution is the photovoltaic welding strip tin alloy immersion plating technology, which is to immerse the welding strip coated with flux into the tin alloy liquid to be dip-plated, and the welding strip moves quickly, so that a layer of tin alloy liquid is dip-plated on the surface. However, this type of immersion plating technology has the following problems: first, the welding strip and the tin alloy liquid are weakly bonded, and the tin alloy layer is prone to fall off. Second, the thickness of the immersion tin alloy layer is very thin, generally 2μm-5μm, and it is difficult to break through the thickness limit, which limits the design space of the composite welding wire composition and has no practical application value. In fact, the current coating or plating technology can only prepare coatings or platings with micro-nano thickness, and there is no effective solution for millimeter-level coatings or platings. This technical solution first realizes the cooling and solidification of the tin-bismuth alloy liquid around the tin-bronze welding wire through local supercooling of the liquid phase, and at the same time uses the laser-arc directional energy deposition technology to cause the solidified tin-bismuth alloy liquid to re-melt to form a liquid phase channel as the movement channel of the tin-bronze welding wire. And the diameter of the composite welding wire is controlled by controlling the size of the bottom hole of the liquid phase channel through laser energy. When the tin-bronze welding wire passes through the liquid phase channel, the tin-bismuth alloy and the tin-bronze welding wire are compounded by the arc. At this time, the bismuth-bronze composite welding wire can not only obtain sufficient tin-bismuth alloy thickness to ensure the composition design requirements, but also achieve high-strength bonding between the tin-bismuth alloy and the tin-bronze, preventing the tin-bismuth alloy layer from falling off during subsequent drawing and use of the composite welding wire.
[0028] 2. The bismuth-bronze composite welding wire has a low-melting-point and high-fluidity tin-bismuth alloy on the outer layer of the tin-bronze welding wire, which significantly improves the wetting and spreading of the edge of the molten pool during the arc cladding process, thereby improving the edge wetting of the single-pass cladding layer. This greatly reduces the porosity defects caused by overlap between the front and rear passes of the arc cladding.
[0029] 3. The addition of trace alloying elements such as Cr, Zr, Ti, and P is beneficial to improving the quality of the arc cladding layer of the composite welding wire. The tendency of pore formation in the cladding layer with the addition of these trace elements is significantly reduced. At the same time, the antioxidant ability is enhanced during the cladding process, and the oxide film on the surface of the cladding layer is reduced.
[0030] 4. The bismuth bronze composite wire obtained by the present invention has good processing plasticity and will not suffer from brittle fracture during the wire forming process.
[0031] 5. The present invention forms a solid phase region by locally cooling the tin-bismuth alloy liquid, and forms a liquid phase channel in the solid phase region by laser arc. The arc melts the solid phase tin-bismuth alloy on the one hand, and composites the tin-bismuth alloy and the tin bronze welding wire on the other hand. The laser action is mainly to form a suitable bottom hole size to obtain the required composite welding wire diameter. At this time, the wire diameter consistency is difficult to meet the use requirements of the welding wire diameter, and the wire diameter needs to be strictly and accurately controlled by drawing. Bi and Cu are separated into welding wires by the above method, and then the bismuth bronze / steel bimetallic material is made by arc cladding process.
[0032] 6. The arc energy in the liquid phase channel region of the present invention melts the tin-bismuth alloy and simultaneously forms a metallurgical bond between the tin-bismuth alloy and the surface of the tin-bronze welding wire. Since the tin-bronze welding wire has a relatively thin wire diameter and the melting point of the tin-bismuth alloy is relatively low, if the arc acts for a long time, it is easy to cause the tin-bronze welding wire to fuse and the tin-bismuth alloy to melt quickly to the bottom hole, making it difficult to form an ideal liquid phase channel. Too low arc energy will also greatly reduce the stability of the arc itself. Therefore, the tungsten needle electrode is a moving electrode that performs a circular motion around the tin-bronze welding wire. The tungsten needle electrode is 6-8mm away from the tin-bronze welding wire, and the rotation speed is 40-80r / min. At this time, the bismuth-bronze composite welding wire continuously compounded through the liquid phase channel can not only obtain a sufficient thickness of the tin-bismuth alloy to ensure that the composition meets the design requirements, but also can achieve a high-strength bond between the tin-bismuth alloy and the tin-bronze, preventing the tin-bismuth alloy layer from falling off during the subsequent drawing and use of the composite welding wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a schematic diagram of the cross-sectional structure of the bismuth bronze composite wire of the present invention;
[0034] Figure 2 It is a schematic diagram of the preparation process of the present invention;
[0035] Figure 3This is a microstructure diagram of the arc cladding layer of bismuth bronze with a Bi content of 2% according to the present invention;
[0036] Figure 4 This is a microstructure diagram of the arc cladding layer of bismuth bronze with a Bi content of 3% according to the present invention;
[0037] Figure 5 This is a microstructure diagram of the arc cladding layer of bismuth bronze with a Bi content of 4% according to the present invention;
[0038] Figure 6 This is a microstructure diagram of the arc cladding layer of bismuth bronze with a Bi content of 6% according to the present invention;
[0039] Figure 7 This is a microstructure diagram of metallographic defects in comparative example 1 when the tungsten needle electrode process is omitted;
[0040] Figure 8 is a metallographic microstructure diagram of Example 1 of the present invention;
[0041] Fig. 9 It is the microstructure diagram of laser cladding metallographic defects. DETAILED DESCRIPTION
[0042] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0043] Example 1
[0044] like Figure 1 As shown, a bismuth-bronze composite wire for arc cladding of sliding bearings includes a two-layer structure: an inner core structure is a tin-bronze welding wire, and an outer layer structure is a tin-bismuth binary alloy layer. The tin-bronze welding wire has a Sn content of 7.24% wt and a remainder of Cu. The tin-bismuth alloy has a Sn content of 70% wt and a Bi content of 30% wt.
[0045] like Figure 2 As shown, a preparation process of a bismuth bronze composite wire for arc cladding of sliding bearings comprises the following steps:
[0046] S1, pass the 2mm diameter tin bronze welding wire through the tin bath;
[0047] S2, turn on the local cooling device to perform a local supercooling process; the supercooling device is set to a temperature of 40°C;
[0048] S3, injecting a tin-bismuth alloy liquid into the tin bath, wherein the Sn content of the tin-bismuth alloy liquid is 70%wt, the Bi content is 30%wt, and the depth of the tin-bismuth alloy liquid in the tin bath is 10 mm;
[0049] S4, after the tin-bismuth alloy liquid around the tin-bronze welding wire solidifies to form a solid-phase tin-bismuth alloy zone, the laser-arc directional energy deposition device is turned on, and a liquid phase channel centered on the tin-bronze welding wire is formed in the solidified tin-bismuth alloy through a laser-arc composite directional energy deposition process (laser power 500W, arc current 60A, voltage 12V), and the tin-bronze welding wire begins to move from top to bottom at a speed of 10mm / s to penetrate the tin-bismuth alloy liquid phase channel; the size of the bottom hole of the liquid phase channel is controlled by adjusting the laser energy to control the diameter of the bismuth-bronze composite welding wire; the tungsten needle electrode is a moving electrode that performs a circular motion around the tin-bronze welding wire, the tungsten needle electrode is 6mm away from the tin-bronze welding wire, and the rotation speed is 40r / min; the thickness of the tin-bismuth alloy layer after composite is 0.04mm;
[0050] S5, drawing the bismuth-bronze composite welding wire to a diameter of 0.8 mm through a drawing process, and the thickness of the tin-bismuth alloy layer after drawing is 0.015 mm; obtaining a bismuth-bronze composite wire for arc cladding of sliding bearings.
[0051] The arc cladding process parameters of the bismuth-bronze composite wire used for arc cladding of sliding bearings in this embodiment are: current 90A, voltage 12V, swing frequency 0.6Hz, swing width 25mm, speed 6cm / min.
[0052] The arc cladding layer of the bismuth bronze composite wire obtained in this embodiment has a composition of 11.76%wt Sn, 2.17%wt Bi, 0.05%wt Cr, and the balance Cu.
[0053] The present embodiment provides an application of a bismuth-bronze composite wire for arc cladding of a sliding bearing in a bearing alloy.
[0054] like Figure 3 As shown in the figure of Example 1, it can be seen that the Bi phase in the arc cladding layer is evenly dispersed in the form of small spheres, proving that the composition of the tin-bismuth alloy layer of the composite welding wire is uniform and the thickness is consistent. Figure 8 As shown, it is the metallographic microstructure diagram of Example 1. The arc cladding layer obtained in this example has no porosity defects.
[0055] Example 2
[0056] A bismuth-bronze composite wire for arc cladding of sliding bearings comprises a two-layer structure: an inner core structure is a tin-bronze welding wire, and an outer layer structure is a tin-bismuth binary alloy layer, wherein the tin-bronze welding wire has a Sn content of 5.95%wt and a remainder of Cu, the tin-bismuth alloy has a Sn content of 60%wt and a Bi content of 40%wt.
[0057] A preparation process of a bismuth bronze composite wire for arc cladding of sliding bearings comprises the following steps:
[0058] S1, pass the 4mm diameter tin bronze welding wire through the tin bath;
[0059] S2, turn on the local cooling device to perform a local supercooling process; the supercooling device is set to a temperature of 45°C;
[0060] S3, injecting a tin-bismuth alloy liquid into the tin bath, wherein the Sn content of the tin-bismuth alloy liquid is 60%wt, the Bi content is 40%wt, and the depth of the tin-bismuth alloy liquid in the tin bath is 5 mm;
[0061] S4, after the tin-bismuth alloy liquid around the tin-bronze welding wire solidifies to form a solid-phase tin-bismuth alloy zone, the laser-arc directional energy deposition device is turned on, and a liquid phase channel centered on the tin-bronze welding wire is formed in the solidified tin-bismuth alloy through a laser-arc composite directional energy deposition process (laser power 300W, arc current 70A, voltage 11V), and the tin-bronze welding wire begins to move from top to bottom at a speed of 5mm / s to penetrate the tin-bismuth alloy liquid phase channel; the size of the bottom hole of the liquid phase channel is controlled by adjusting the laser energy to control the diameter of the bismuth-bronze composite welding wire; the tungsten needle electrode is a moving electrode that performs a circular motion around the tin-bronze welding wire, the tungsten needle electrode is 8mm away from the tin-bronze welding wire, and the rotation speed is 80r / min; the thickness of the tin-bismuth alloy layer after composite is 0.08mm;
[0062] S5, the bismuth-bronze composite welding wire is drawn to a diameter of 1.6 mm through a drawing process, and the thickness of the tin-bismuth alloy layer after drawing is 0.03 mm, thereby obtaining a bismuth-bronze composite wire for arc cladding of sliding bearings.
[0063] The arc cladding process parameters of the bismuth-bronze composite wire used for arc cladding of sliding bearings in this embodiment are: current 90A, voltage 12V, swing frequency 0.6Hz, swing width 25mm, speed 6cm / min.
[0064] The arc cladding layer of the bismuth bronze composite wire obtained in this embodiment has a composition of 9.95%wt Sn, 3.07%wt Bi, 0.02%wt Cr, 0.02%wt Zr, 0.02%wt Ti, 0.02%wt P, and the balance Cu.
[0065] The present embodiment provides an application of a bismuth-bronze composite wire for arc cladding of a sliding bearing in a bearing alloy.
[0066] like Figure 4 As shown in the figure of Example 2, it can be seen that the Bi phase in the arc cladding layer is uniformly dispersed in the form of small spheres, proving that the composition of the composite welding wire tin-bismuth alloy layer is uniform and the thickness is consistent. As the Bi content increases, the size of the Bi phase increases.
[0067] Example 3
[0068] A bismuth-bronze composite wire for arc cladding of sliding bearings comprises a two-layer structure: an inner core structure is a tin-bronze welding wire, and an outer layer structure is a tin-bismuth binary alloy layer, wherein the tin-bronze welding wire has a Sn content of 4.36%wt and a remainder of Cu, the tin-bismuth alloy has a Sn content of 50%wt, and a Bi content of 50%wt.
[0069] A preparation process of a bismuth bronze composite wire for arc cladding of sliding bearings comprises the following steps:
[0070] S1, pass the 3mm diameter tin bronze welding wire through the tin bath;
[0071] S2, turn on the local cooling device to perform a local supercooling process; the supercooling device is set to a temperature of 45°C;
[0072] S3, injecting a tin-bismuth alloy liquid into the tin bath, wherein the Sn content of the tin-bismuth alloy liquid is 50%wt, the Bi content is 50%wt, and the depth of the tin-bismuth alloy liquid in the tin bath is 8 mm;
[0073] S4, after the tin-bismuth alloy liquid around the tin-bronze welding wire solidifies to form a solid-phase tin-bismuth alloy zone, the laser-arc directional energy deposition device is turned on, and a liquid phase channel centered on the tin-bronze welding wire is formed in the solidified tin-bismuth alloy through a laser-arc composite directional energy deposition process (laser power 600W, arc current 65A, voltage 11V), and the tin-bronze welding wire begins to move from top to bottom at a speed of 15mm / s to penetrate the tin-bismuth alloy liquid phase channel; the size of the bottom hole of the liquid phase channel is controlled by adjusting the laser energy to control the diameter of the bismuth-bronze composite welding wire; the tungsten needle electrode is a moving electrode that performs a circular motion around the tin-bronze welding wire, the tungsten needle electrode is 7mm away from the tin-bronze welding wire, and the rotation speed is 50r / min; the thickness of the tin-bismuth alloy layer after composite is 0.06mm;
[0074] S5, drawing the bismuth-bronze composite welding wire to a diameter of 1.00 mm through a drawing process, and the thickness of the tin-bismuth alloy layer after drawing is 0.022 mm; obtaining a bismuth-bronze composite wire for arc cladding of sliding bearings.
[0075] The arc cladding process parameters of the bismuth-bronze composite wire used for arc cladding of sliding bearings in this embodiment are: current 90A, voltage 12V, swing frequency 0.6Hz, swing width 25mm, speed 6cm / min.
[0076] The composition of the arc cladding layer of the bismuth bronze composite wire obtained in this embodiment is 7.86%wt Sn, 3.84%wt Bi, and the balance is Cu.
[0077] The present embodiment provides an application of a bismuth-bronze composite wire for arc cladding of a sliding bearing in a bearing alloy.
[0078] like Figure 5As shown in the figure of Example 3, it can be seen that the Bi phase in the arc cladding layer is uniformly dispersed in the form of small spheres, proving that the composition of the composite welding wire tin-bismuth alloy layer is uniform and the thickness is consistent. As the Bi content increases, the size of the Bi phase increases further and the distribution becomes more dense.
[0079] Example 4
[0080] A bismuth-bronze composite wire for arc cladding of sliding bearings comprises a two-layer structure: an inner core structure is a tin-bronze welding wire, and an outer layer structure is a tin-bismuth binary alloy layer, wherein the tin-bronze welding wire has a Sn content of 4.36%wt, the remainder is Cu, the tin-bismuth alloy has a Sn content of 30%wt, and the Bi content is 70%wt.
[0081] A preparation process of a bismuth bronze composite wire for arc cladding of sliding bearings comprises the following steps:
[0082] S1, pass the tin bronze wire with a diameter of 3.5 mm through the tin bath;
[0083] S2, turn on the local cooling device to perform a local supercooling process; the supercooling device is set to a temperature of 40°C;
[0084] S3, injecting a tin-bismuth alloy liquid into the tin bath, wherein the Sn content of the tin-bismuth alloy liquid is 30%wt, the Bi content is 70%wt, and the depth of the tin-bismuth alloy liquid in the tin bath is 10 mm;
[0085] S4, after the tin-bismuth alloy liquid around the tin-bronze welding wire solidifies to form a solid-phase tin-bismuth alloy zone, the laser-arc directional energy deposition device is turned on, and a liquid phase channel centered on the tin-bronze welding wire is formed in the solidified tin-bismuth alloy through a laser-arc composite directional energy deposition process (laser power 500W, arc current 60A, voltage 12V), and the tin-bronze welding wire begins to move from top to bottom at a speed of 10mm / s to penetrate the tin-bismuth alloy liquid phase channel; the size of the bottom hole of the liquid phase channel is controlled by adjusting the laser energy to control the diameter of the bismuth-bronze composite welding wire; the tungsten needle electrode is a moving electrode that performs a circular motion around the tin-bronze welding wire, the tungsten needle electrode is 6mm away from the tin-bronze welding wire, and the rotation speed is 60r / min; the thickness of the tin-bismuth alloy layer after composite is 0.07mm;
[0086] S5, the bismuth-bronze composite welding wire is drawn to a diameter of 0.9 mm through a drawing process, and the thickness of the tin-bismuth alloy layer after drawing is 0.027 mm; and a bismuth-bronze composite wire for arc cladding of sliding bearings is obtained.
[0087] The arc cladding process parameters of the bismuth-bronze composite wire used for arc cladding of sliding bearings in this embodiment are: current 90A, voltage 12V, swing frequency 0.6Hz, swing width 25mm, speed 6cm / min.
[0088] The composition of the arc cladding layer of the bismuth-bronze composite wire obtained in this embodiment is 6.43%wt Sn, 5.66%wt Bi, and the balance is Cu.
[0089] The present embodiment provides an application of a bismuth-bronze composite wire for arc cladding of a sliding bearing in a bearing alloy.
[0090] like Figure 6 As shown in the figure of Example 4, it can be seen that the Bi phase in the arc cladding layer is uniformly dispersed in the form of small spheres, proving that the composition of the composite welding wire tin-bismuth alloy layer is uniform and the thickness is consistent. The reduction of Sn content increases the melting point of the alloy, accelerates the solidification of the alloy, and the size of the Bi phase does not increase further, but is densely distributed in the form of fine particles.
[0091] Comparative Example 1
[0092] Compared with Example 1, Comparative Example 1 omits the tungsten needle electrode process, and the rest are the same. Compared with Example 1, the arc cladding layer of Comparative Example 1 is prone to pore defects (specifically, Figure 7 shown).
[0093] Comparative Example 2
[0094] like Fig. 9 As shown in the figure, laser cladding of copper alloy powder is prone to porosity defects in the cladding layer due to factors such as the scattering of laser by copper alloy and oxidation of the powder itself.
[0095] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.
[0096] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.
[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A bismuth bronze composite wire for arc cladding of sliding bearings, characterized in that: The bismuth bronze composite wire comprises a two-layer structure, calculated by weight percentage: The inner core structure is tin bronze, with Sn content of 4.36%-7.24% and the balance being Cu; The outer layer structure is a tin-bismuth binary alloy layer, wherein the Sn content is 30%-70%wt, and the Bi content is 30%-70%wt.
2. The process for preparing a bismuth bronze composite wire for arc cladding of sliding bearings according to claim 1, characterized in that: The following steps are involved: S1, pass the tin bronze wire through the tin bath; S2, start the local cooling device to perform a local supercooling process; S3, injecting tin-bismuth alloy liquid into the tin bath; S4, after the tin-bismuth alloy liquid around the tin-bronze welding wire solidifies to form a solid-phase tin-bismuth alloy zone, the laser-arc directional energy deposition device is turned on, and a liquid phase channel centered on the tin-bronze welding wire is formed in the solidified tin-bismuth alloy through the laser-arc composite directional energy deposition process, and the tin-bronze welding wire begins to move from top to bottom at a speed of 5mm / s-15mm / s; the size of the bottom hole of the liquid phase channel is controlled by adjusting the laser energy to control the wire diameter of the bismuth-bronze composite welding wire; the tungsten needle electrode is a moving electrode that performs a circular motion around the tin-bronze welding wire, the tungsten needle electrode is 6-8mm away from the tin-bronze welding wire, and the rotation speed is 40-80r / min; S5, drawing the bismuth-bronze composite welding wire to a diameter of 0.8-1.6 mm through a drawing process to obtain a bismuth-bronze composite wire for arc cladding of sliding bearings.
3. The preparation process according to claim 2, characterized in that: The temperature of the local supercooling process is 40-45°C.
4. The preparation process according to claim 2, characterized in that: The diameter of tin bronze welding wire is 2-4mm.
5. The preparation process according to claim 2, characterized in that: The Sn content in the tin-bismuth alloy liquid is 30%-70%wt, the Bi content is 30%-70%wt, and the depth of the tin-bismuth alloy liquid in the tin bath is 5mm-10mm.
6. The preparation process according to claim 2, characterized in that: The laser power of the laser-arc composite directional energy deposition process is 300W-600W, the arc current is 60A-70A, and the voltage is 11V-12V. The directional method is that the arc acts fixedly toward the solid phase tin-bismuth alloy area, and the laser acts fixedly toward the bottom hole direction.
7. The arc cladding process of bismuth bronze composite wire for arc cladding of sliding bearings according to claim 1, characterized in that: Current 90A, voltage 12V, swing frequency 0.6Hz, swing width 25mm, speed 6cm / min.
8. The arc cladding layer obtained by the arc cladding process according to claim 7 is characterized in that: Calculated by weight percentage, its composition is: Bi: 2.17-5.66%, Sn: 6.43-11.76%, and the balance is Cu.
9. The arc cladding layer obtained by the arc cladding process according to claim 7, characterized in that: The arc cladding layer also includes one or more of Cr, Zr, Ti and P. In terms of weight percentage, the total content of one or more of Cr, Zr, Ti and P is 0.05-0.08%.
10. Use of the bismuth bronze composite wire for arc cladding of sliding bearings according to claim 1 in bearing alloys.
Citation Information
Patent Citations
Nuclear shell structure Pb-free solder ball for electronic packaging and preparation method thereof
CN101642858A
Sn-Bi / Cu lead-free hybrid welding material
CN104985350A
Conductive welding wire for solar cell and preparation method thereof
CN106825981A
Method for preparing bearing bush base material through lead-tin bronze arc deposition
CN113172314A
Interconnection structural member, photovoltaic module with interconnection structural member and processing method of interconnection structural member
CN114068749A